Analisis Pengaruh Variasi Rasio Komposisi Ampas Tebu Dan Arang Tempurung Kelapa Terhadap Karakteristik Briket - Muhammad Firmansyah Suherman; Rico Aditia Prahmana; Achmad Gus Fahmi; Lathifa Putri Afisna; Farid Jayadi; Devia Gahana Cindi Alvian; Pathur Razi Ansyah (Institut Teknologi Dirgantara Adisutjipto, 2026)
In Indonesia, basic energy needs still depend on natural gas, coal, and petroleum until their availability is decreasing. Bagasse and coconut shell charcoal briquettes offer the best solution as an alternative energy source that is environmentally friendly and abundantly available. This study aims to analyze the effect of variations in the composition of bagasse (AT) and coconut shell charcoal (TK) using tapioca starch adhesive on the characteristics of the briquettes. The compositions tested were 25% AT : 75% TK; 30% AT : 70% TK; 35% AT : 65% TK. The briquettes were evaluated based on parameters such as calorific value, carbon content, ash content, water content, volatile matter content, and combustion rate. The results showed that the briquettes with composition variations of 25% bagasse and 75% coconut shell charcoal had a calorific value of 5721.63 cal/g, carbon content of 64%, ash content of 8%, water content of 7.56%, volatile matter content of 28%, and a combustion rate of 0.19 grams/minute. However, only the water content value that meets SNI 1683/2021 quality 1 is ≤ 8%